A Descriptive Comparative Analysis of the Surgical Management of Adrenal Tumors: The Open, Robotic, and Laparoscopic Approaches - Al-Thani, Hassan; Al-Thani, Noora; Al-Sulaiti, Maryam; Tabeb, Abdelhakem; Asim, Mohammad; El-Menyar, Ayman (Frontiers in Surgery, 2022)
Background: Currently, adrenalectomies are trending towards minimally invasive approach including robotic and laparoscopic surgery. We aimed to describe the clinical presentation and outcomes associated with the 3 different surgical approaches in patients who underwent adrenalectomy for adrenal mass at a single tertiary center. Methods: A retrospective descriptive observational study was conducted to include all patients who underwent surgical interventions for adrenal gland mass between 2004 and 2019. Patients were categorized into three groups according to the interventional approach (open, robotic versus laparoscopic adrenalectomy) and data were analyzed and compared. Results: A total of 124 patients underwent adrenalectomies (61.3% robotic, 22.6% open and 16.1% laparoscopic approach). Incidentally discovered adrenal mass was reported in 67% of patients and hypertension was the most prevalent comorbidity (53%). The tendency for malignancy increased with increasing the tumor size while the functioning tumors were more in the smaller tumor size. Larger tumors were more common in the younger patients. The robotic approach showed shorter surgical intensive care and hospital length of stay. Patients in the open adrenalectomy group frequently presented with abdominal pain (p=0.001), had more nonfunctional adrenal mass (p=0.04), larger mean tumor size (p=0.001), and were frequently operated on the right side (p=0.03). There was no post-operative mortality; however, during follow-up, 8 patients died (3 open, 3 laparoscopic and 1 robotic approach). The median follow-up was 746 days (range 7-5840). Conclusions: The study explored the three surgical adrenalectomy approaches in a dedicated center for patients with adrenal pathology. It showed that robotic adrenalectomy could be safe and effective surgical approach for patients with benign functioning adrenal tumors of a diameter less than < 6 cm. However, the choice of a surgical approach varies according to the adrenal mass presentation, patient fitness for surgery, type and sizes of the tumor, surgeon’s experience and hospital resources. Open surgery is considered the first choice for larger, ruptured adrenal tumor or malignancy. However, the recent restructuring of the surgical department resulted in selection bias in favor of the robotic surgery. Further studies are required to address the risk factors, selection criteria for appropriate management, cost and quality of life.